Dehalococcoides mccartyi strain CBDB1 takes up protons from the cytoplasm to reductively dehalogenate organohalides indicating a new modus of proton motive force generation - Hellmold, Nadine; Eberwein, Marie; Phan, My Hanh Thi; Kümmel, Steffen; Einsle, Oliver; Deobald, Darja; Adrian, Lorenz (Frontiers in Microbiology, 2023)
Proton translocation across the cytoplasmic membrane is a vital process for all organisms.Dehalococcoides strains are strictly anaerobic organohalide respiring bacteria that lack quinones and cytochromes but express a large membrane-bound protein complex (OHR complex) proposed to generate a proton gradient. However, its functioning is unclear. By using a dehalogenase-based enzyme activity assay with deuterium-labelled water in various experimental designs, we obtained evidence that the halogen atom of the halogenated electron acceptor is substituted with a proton from the cytoplasm. This suggests that the protein complex couples exergonic electron flux through the periplasmic subunits of the OHR complex to the endergonic transport of protons from the cytoplasm across the cytoplasmic membrane against the proton gradient to the halogenated electron acceptor.Using computational tools, we located two proton-conducting half-channels in the AlphaFold2predicted structure of the OmeB subunit of the OHR complex, converging in a highly conserved arginine residue that could play a proton gatekeeper role. The cytoplasmic proton half-channel in OmeB is connected to a putative proton-conducting path within the reductive dehalogenase subunit.Our results indicate that the reductive dehalogenase and its halogenated substrate serve as both electron and proton acceptors, providing insights into the proton translocation mechanism within the OHR complex and contributing to a better understanding of energy conservation in D. mccartyi strains. Our results reveal a very simple mode of energy conservation in anaerobic bacteria, showing that proton translocation coupled to periplasmic electron flow might have importance also in other microbial processes and biotechnological applications.